(untitled) (Materiali di Estetica. Terza serie, 2019)
This article develops the theme of the umanesimo rigenerato, a life’s vision which finds its foundation in the relationship between God and man as matter of the be and the being of the all humanity. It emerges the centrality of the cuore and of the sentire which is able to catch the life quality’s unit through a phenomenological approach to the faith’s experience. Edith Stein, a german thinker of the XX century, becomes witness of this umanesimo rigenerato, whose ontological foundation reveals itself to the human being in those unique experience which is the Cross’ passion.